Captain Preston B. Haines and Captain Richard D. Kirkpatrick, USMC, E1940 and USN ROTC Flag, 1942 (Tufts Archival Research Center, 2005)
5 x 7; 5 x 7 mounted on 10 x 12 paper in M.S. Munro, Photographic History of Tufts College Volume 74 pg. 100